An Overview of Democratic Consolidation and Regression in Africa - Muhammad, Abdulrasheed; Fanny-Kinge, Ruth (Department of International Relations, Hasanuddin University, 2024)
Democratic rule in Africa has been characterized by uneasiness resulting from autocratic tendencies in some of the countries. From the 1990s and due to a host of factors, African countries began to experience new lease of democratization with high hopes which soon turned out to be an illusion arising from series of developments within and outside the continent. Against this background, this paper examines dimensions of democratic rule in Africa noting its tendencies towards consolidation and regression as it manifests in different countries as well as factors that are responsible for the observed trend. Data for the study is obtained from secondary sources through examination of copious literature on the subject and examining occurrences in different parts of the continent. It is concluded that the region experienced overall, though uneven and not substantial progress towards democratization. While some have experienced tendency towards backsliding, some others have experienced considerable growth in some of the indexes that promote democratic consolidation. On the aggregate however, the continent cannot be said to be making substantial progress towards consolidation. This may be due to a host of factors that include peculiar political environment of each country. It thus recommended that African leaders need to introduce reforms that would cut across the different facets of the continent and that will take into account the specific character of each African country rather than the adoption of a policy based on its success in a different socio-political environment.